2022
DOI: 10.1038/s41419-022-05254-1
|View full text |Cite
|
Sign up to set email alerts
|

Circ_CEA promotes the interaction between the p53 and cyclin-dependent kinases 1 as a scaffold to inhibit the apoptosis of gastric cancer

Abstract: Circular RNAs (circRNAs) have been reported to play essential roles in tumorigenesis and progression. This study aimed to identify dysregulated circRNAs in gastric cancer (GC) and investigate the functions and underlying mechanism of these circRNAs in GC development. Here, we identify circ_CEA, a circRNA derived from the back-splicing of CEA cell adhesion molecule 5 (CEA) gene, as a novel oncogenic driver of GC. Circ_CEA is significantly upregulated in GC tissues and cell lines. Circ_CEA knockdown suppresses G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Circ_CEA is significantly upregulated in GC tissues and cell lines, wherein it serves as a scaffold to facilitate the interaction between p53 and cyclin-dependent kinase 1, which phosphorylates p53 at Ser315, decreases its retention in the nucleus, and suppresses its activity. Consequently, p53 target genes associated with apoptosis are downregulated and GC cell apoptosis is inhibited [ 37 ].…”
Section: Circrnas Contribute To Tumorigenesis and Progression Of Gc T...mentioning
confidence: 99%
“…Circ_CEA is significantly upregulated in GC tissues and cell lines, wherein it serves as a scaffold to facilitate the interaction between p53 and cyclin-dependent kinase 1, which phosphorylates p53 at Ser315, decreases its retention in the nucleus, and suppresses its activity. Consequently, p53 target genes associated with apoptosis are downregulated and GC cell apoptosis is inhibited [ 37 ].…”
Section: Circrnas Contribute To Tumorigenesis and Progression Of Gc T...mentioning
confidence: 99%
“…CircCEA may act as a scaffold between p53 and cyclin‐dependent kinases 1 (CDK1), according to a study. It promoted CDK1‐mediated p53 phosphorylation, which decreased p53's nuclear retention and hindered its function, ultimately resulting in p53 downregulation 108 . Liu et al 109 found that circMYH9 disrupted the stability of p53 pre‐mRNA by recruiting hnRNPA2B1, which played a stabilizing role in the nucleus by binding to N6‐methyladenosine sites of p53 pre‐mRNA.…”
Section: Circular Rnas Regulate Cellular Senescence Via Various Pathwaysmentioning
confidence: 99%
“…(2) CircRNAs serve as molecular sponges for proteins, particularly RNA-binding proteins, regulating the transcription or translation of downstream target genes ( 22 , 23 ). (3) CircRNAs function as protein scaffolds facilitating interactions between specific proteins ( 16 , 24 ). (4) CircRNAs possess translational capacity, producing peptides that exert biological functions ( 25 27 ).…”
Section: Introductionmentioning
confidence: 99%